The Norwegian mediation in the Venezuelan internal crisis as a single procedure from 2019 to the present - Antialón Conde, Alexander (2022)
This article explores some theoretical and procedural aspects of the Norwegian mediation in the Venezuelan internal crisis. Likewise, it tries to demonstrate that it is not a mediation of 2019 and another of 2021, but that it consists of a single mediation with a suspension, an interruption and a resumption. This mediation (legal term) or facilitation (political term) has been carried out to date, based in Mexico and with the Netherlands and Russia as accompanying countries.